Low testosterone levels predict clinical adverse outcomes in SARS‐CoV‐2 pneumonia patients. (3rd June 2020) - Rastrelli, Giulia; Di Stasi, Vincenza; Inglese, Francesco; Beccaria, Massimiliano; Garuti, Martina; Di Costanzo, Domenica; Spreafico, Fabio; Greco, Graziana Francesca; Cervi, Giulia; Pecoriello, Antonietta; Magini, Angela; Todisco, Tommaso; et al.
Abstract: Background: The pandemic of new severe acute respiratory syndrome (SARS) due to coronavirus (CoV) 2 (SARS‐CoV‐2) has stressed the importance of effective diagnostic and prognostic biomarkers of clinical worsening and mortality. Epidemiological data showing a differential impact of SARS‐CoV‐2 infection on women and men have suggested a potential role for testosterone (T) in determining gender disparity in the SARS‐CoV‐2 clinical outcomes. Objectives: To estimate the association between T level and SARS‐CoV‐2 clinical outcomes (defined as conditions requiring transfer to higher or lower intensity of care or death) in a cohort of patients admitted in the respiratory intensive care unit (RICU). Materials and methods: A consecutive series of 31 male patients affected by SARS‐CoV‐2 pneumonia and recovered in the respiratory intensive care unit (RICU) of the "Carlo Poma" Hospital in Mantua were analyzed. Several biochemical risk factors (ie, blood count and leukocyte formula, C‐reactive protein (CRP), procalcitonin (PCT), lactate dehydrogenase (LDH), ferritin, D‐dimer, fibrinogen, interleukin 6 (IL‐6)) as well as total testosterone (TT), calculated free T (cFT), sex hormone–binding globulin (SHBG), and luteinizing hormone (LH) were determined. Results: Lower TT and cFT were found in the transferred to ICU/deceased in RICU group vs groups of patients transferred to IM or maintained in the RICU in stable condition. Both TT and cFT showed a negative significant correlation with biochemical risk factors (ie, the neutrophil count, LDH, and PCT) but a positive association with the lymphocyte count. Likewise, TT was also negatively associated with CRP and ferritin levels. A steep increase in both ICU transfer and mortality risk was observed in men with TT < 5 nmol/L or cFT < 100 pmol/L. Discussion and conclusion: Our study demonstrates for the first time that lower baseline levels of TT and cFT levels predict poor prognosis and mortality in SARS‐CoV‐2‐infected men admitted to RICU.